2008
DOI: 10.1177/1934578x0800300418
|View full text |Cite
|
Sign up to set email alerts
|

Germacrone: Occurrence, Synthesis, Chemical Transformations and Biological Properties

Abstract: This paper is dedicated to Professor Pedro Joseph-Nathan for his 65 th birthday. Germacrone (1) forms part of a great number of essential oils, in some of them comprising more than 20% of the total oil. This compound presents a wide range of biological activities (CNS depressant, antiinflammatory, antiulcer, antifeedant, antibacterial, antifungal, antitumor, antitussive, vasodilator, choleretic, hepatoprotector), which are analyzed. The chemical reactivity of germacrone, including cyclization reactions, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…The structure of a related molecule, isogermacrone, has also been reported (Jacobsson et al , 1985; CSD Refcode DICDOI). The FIQLOG structure is in space group Pc , and apparently is an example of a chiral structure formed by a cycloalkene molecule, which does not contain chiral centers (Barrero et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of a related molecule, isogermacrone, has also been reported (Jacobsson et al , 1985; CSD Refcode DICDOI). The FIQLOG structure is in space group Pc , and apparently is an example of a chiral structure formed by a cycloalkene molecule, which does not contain chiral centers (Barrero et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…and tumeric ( Curcuma spp .) which are commonly used as food spices and flavoring agents ( 165 , 166 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, germacrone and b-elemene are bioactive components occurring in the essential oils from Rhizoma curcuma (known as Ezhu), one of the most used traditional Chinese medicines, especially in the treatment of cancer and stomach complaints (Zhong, Hoi et al, 2011). In previous studies, germacrone was reported to have anti-inflammatory activity, depressant properties on the central nervous system, inhibition of stressinduced ulcers, hepatoprotective effects, vasodilator activity and inhibition of breast cancer cell line proliferation (Barrero, Herrador, Arteaga, & Catalàn, 2008).…”
Section: Gc Analysismentioning
confidence: 99%